Analisis Penerapan Marketing Mix Untuk Meningkatkan Penjualan UMKM Kerajinan Kayu UD. Rizky - Rohma, Hindun Miftakhur; Mardani, Ronny Malavia; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the implementation of the marketing mix strategy in increasing sales of wooden craft UMKM. The marketing mix, which consists of product, price, place, and promotion element, plays a crucial role in determining the competitiveness and success of UMKM. This research employs a qualitative method with a descriptive approach, where data is collected through interviews, observations, and documentation. The findings indicate that a well-implemented marketing mix strategy can enhance sales volume. However, challenges remain in the promotion aspect, particularly in the utilization of digital media. Therefore, UMKM needs to improve their digital marketing strategies to reach a broader market. Keywords: Marketing mix, UMKM, marketing strategy, sales improvement.